1995
DOI: 10.1590/s0004-282x1995000200022
|View full text |Cite
|
Sign up to set email alerts
|

Dopa-sensitive progressive dystonia of childhood with diurnal fluctuations of symptoms: a case report

Abstract: SUMMARY -Progressive dystonia with diurnal fluctuations sensitive to levodopa, also known as Segawa's disease, is a rare form of autosomal dominant extrapyramidal disease in the pediatric age group. The dystonic and Parkinson-like symptoms are the main clinical features of the disease and, characteristically but not in all cases, show a diurnal variation. They are absent or present to a lesser extent in the morning, worsening during the day. Treatment with small doses of levodopa results in remission or marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
(4 reference statements)
0
3
0
1
Order By: Relevance
“…A class IV trial performed on a small sample of dopa‐responsive dystonia patients showed no differences in the short‐ and long‐duration responses [88]. Many uncontrolled studies reported improvement of Parkinsonism and dystonia with variable doses of levodopa, from 100 mg daily [89] to 750 mg daily [90]. In a case series of 20 patients, clinical benefit was observed at a mean dose of 343.8 mg daily for patients with dyskinesias, and 189.1 mg daily for patients without dyskinesias; in addition, there was an inverse correlation between the daily dose of levodopa and duration of treatment [91].…”
Section: Dopaminergic Drugsmentioning
confidence: 99%
“…A class IV trial performed on a small sample of dopa‐responsive dystonia patients showed no differences in the short‐ and long‐duration responses [88]. Many uncontrolled studies reported improvement of Parkinsonism and dystonia with variable doses of levodopa, from 100 mg daily [89] to 750 mg daily [90]. In a case series of 20 patients, clinical benefit was observed at a mean dose of 343.8 mg daily for patients with dyskinesias, and 189.1 mg daily for patients without dyskinesias; in addition, there was an inverse correlation between the daily dose of levodopa and duration of treatment [91].…”
Section: Dopaminergic Drugsmentioning
confidence: 99%
“…De la Fuente-Fernandez reported adequate control with a daily dose of 250 mg of levodopa [26] while Wang et al suggested an optimal dose of 10 mg/kg [27]. Others have reported control with 20 mg/kg (28) or 100 mg/d (29). Early treatment can prevent complications such as contracture formation and fixed equinovarus foot deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies found that the typical diurnal fluctuation is not constant (Deonna 1986, Rondot et al 1992, Segawa et al 2003). Treatment with low-dose levodopa usually brings about a dramatic improvement, which is often maintained over periods ranging from 1 to 10 years with no adverse effects (Segawa et al 1990, Nygaard et al 1992, Gherpelli et al 1995. Recurrence of symptoms on withdrawal was observed in all patients in whom low-dose levadopa was administered.…”
Section: Introductionmentioning
confidence: 93%